Sociodemographic Characteristics of Premature Birth in Sleman Regency - Utami, Dianita Putri; Ratrikaningtyas, Prima Dhewi; Oktaria, Vicka (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2024)
Background: Premature birth can increase mortality and disability in infants. Premature birth can be influenced by several types of factors, such as sociodemographic factors. Based on literature studies, there are several contradictory research results regarding the sociodemographic characteristics of premature birth. In addition, there is a surveillance system HDSS Sleman that periodically collects data on demographic transition, health status, and social transition in Sleman.Objective: This research objective is determining the sociodemographic characteristics of premature birth in Sleman Regency.Method: This is a cross-sectional study with total sampling method using HDSS Sleman secondary data from cycle 4 (2018) until cycle 6 (2020).Results and Discussion: The results of this study showed that the total proportion of premature birth in Sleman Regency from 2018 to 2020 was 14.4%. Then, the proportion of premature birth each year from 2018 to 2020 were 18.5%, 13.0%, and 5.8% respectively. After that, the highest proportion of sociodemographic characteristics of the mothers experiencing premature birth were in the category of maternal age <20 years old (20.0%), maternal parity 1 (13.0%), “working” occupational status (15.4%), low educational status (18.8%), and low socioeconomic status (18.0%).Conclusion: It can be concluded that the most common sociodemographic characteristics of the mothers experiencing premature birth were maternal age <20 years old, maternal parity 1, “working” occupational status, low educational status, and low socioeconomic status.